Hegemonic signs in the film Ex-Machina: robotization and control - Morales Campos, Arturo (2020)
Through socio-semiotics theory, the film Ex-Machina (Garland, 2015) contains some hegemonic signs which could be linked to the human robotization phenomenon. Within that fictional strategy of the film, we find political and commercial ideologies. These ideologies can be materialized in two proposals: transhumanism and moral bio-enhancement. Specifically, part of the current research devoted to increasing human capacities is directed towards a new and deeper social division of a Darwinian nature: on the one hand, the attractive possibility of overcoming the “obsolete” human body, on the other, the distribution of drugs to produce docile and “ethical” humans.